2017
DOI: 10.1155/2017/4052094
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution oftrans-Resveratrol and Its Metabolites after Oral Administration in Human Eyes

Abstract: Purpose. This study was performed to measure the concentration of trans-resveratrol and its three metabolites in human eyes. Methods. The patients who underwent pars plana vitrectomy for rhegmatogenous retinal detachment were included. The participants were orally given trans-resveratrol-based supplement (Longevinex®). A suitable amount of conjunctiva, aqueous humor, and vitreous humor were obtained during the operation. High-performance liquid chromatography (HPLC) with mass spectrometry (LC/MS/MS) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…It has been shown to get rapidly absorbed, both in vivo, in human studies, and in vitro, in cell culture studies with no marked toxicity reported [11,20]. Resveratrol can penetrate the blood-brain and blood-ocular (retinal-and aqueous) barriers, and it has been detected in the intraocular fluids after oral administration [5,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to get rapidly absorbed, both in vivo, in human studies, and in vitro, in cell culture studies with no marked toxicity reported [11,20]. Resveratrol can penetrate the blood-brain and blood-ocular (retinal-and aqueous) barriers, and it has been detected in the intraocular fluids after oral administration [5,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of the disease, abnormalities in the RPE and Bruch's membrane are present and are followed by further degeneration as the disease progresses [4]. The accumulation of damaged proteins in RPE cells is considered a contributing factor for RPE dysfunction in AMD [5]. Impaired or insufficient autophagy activity in aged cells is involved in many diseases, including inflammatory-, neurodegenerative-, heart-diseases and cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol sulfation was significantly higher in 12 out of 13 breast cancer tissue samples, and these samples showed a 33.5‐fold higher formation rate as compared with their nontumor counterparts. In a recent study , resveratrol‐3‐ O ‐sulfate was determined as the main metabolite of resveratrol in human eye tissues in the conjunctiva, aqueous humor, and vitreous humor, in which the average concentrations of this metabolite were 22.3 nmol/g, 364.9 nM, and 63.0 nM, respectively. At low physiological dose (3–30 μM), resveratrol is rapidly metabolized into its sulfated form in a dose‐dependent fashion in human adipocytes, and SULT1A1 was found as the key enzyme in adipocytes responsible for the biotransformation of resveratrol .…”
Section: Metabolism Of Resveratrol and Pterostilbenementioning
confidence: 99%
“…The metabolites of nobiletin identified in urine of mice after oral administration are 3 0 -demethylnobiletin (3 0 -hydroxy-5,6,7,8,4 0 -pentamethoxyflavone), 4 0 -demethylnobiletin (4 0hydroxy-5,6,7,8,3 0 -pentamethoxyflavone), and 3 0 ,4 0 -didemethylnobiletin (3 0 4 0 -dihydroxy-5,6,7,8-tetramethoxyflavone) [20], which indicates it undergoes mono-demethylation and didemethylation (3 0 ,4 0 -didemethylnobiletin) metabolism in vivo. A recent study showed nobiletin to be extensively metabolized in the small intestine to glucuronide and sulfate conjugates of 3 0 -demethylnobiletin, 4 0 -demethylnobiletin, and 3 0 ,4 0 -didemethylnobiletin, and these conjugates further underwent deconjugation by colonic microflora and were finally distributed into different tissues including liver, small intestine, spleen and colon, but the amount of each metabolite was different [47]. These hydroxylated metabolites showed more potent antiinflammatory and anti-atherogenic activity than nobiletin and little is known about their anti-cancer effects.…”
Section: Anti-cancermentioning
confidence: 99%